Neurotoxic Complications of Contrast CT - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Four children, ages 4-10 yrs, with brain tumors treated at the Univ of Calgary, Alberta, Canada, developed alterations in consciousness and vital signs after contrast-enhanced cranial computed tomography (CT).